O mínimo existencial e a tributação dos produtos da cesta básica no Brasil - Oliveira, Aline Milanski de (2021)
The present study is dedicated to the idea for the realization of the existential minimum in Brazil through the issue of taxation on products belonging to the basic food basket, which are considered necessary goods for the person's existence, so that the tax relief against the tax burden of the person is promoted State. What is evident in the Brazilian reality is the disproportionate increase in the price of consumer goods essential for survival, due to the lack of imposition of limits on the State's taxing power. Thus, the theory of the existential minimum in taxation takes on an aspect when the subject refers to the search for adequate food for the entire population, forming a set of vital goods that need protection against the arbitrariness of the State, considering the abusive tax burden. In this context, we seek to analyze the criterion for applying the existential minimum to products included in the Brazilian basic food basket, indicating ways to reduce the tax burden, in the face of essential products for life, to ensure decent conditions for all citizens and, therefore, to avoid abuses of economic power under the responsibility of the State, using, for this purpose, the theory of the existential minimum, in the tax area, to justify the non-taxation of products that make up the Brazilian basic food basket, as a way to guarantee the implementation of fundamental rights, in particular the principle of human dignity. It was found that, although there is a bill pending in the national legislature to exempt the taxation of these products, it is not a guarantee that these essential goods are permanently protected, so that taxation can be increased, at any time, through policies public, making it necessary to apply the institute of immunity or non-taxation. Finally, the implementation of the minimum existential in the tax sphere on essential goods for human survival must be aimed at the social purpose, thus ensuring protection and effective applicability of human rights based on a humanized justice that promotes equity.